Structural modulation induced by MIIIA metals in Ba3MQ4X (M = Al, Ga, In; Q = S, Se; X = Cl, Br): an experimental and computational analysis. Issue 33 (7th August 2019) - Tudi, Abudukadi; Han, Shujuan; Abudurusuli, Ailijiang; Yu, Haohai; Yang, Zhihua; Pan, Shilie
Abstract : The optical properties of Ba3 MQ4 X (M = Al, Ga, In; Q = S, Se; X = Cl, Br) have been studied and their structures have been compared. Abstract : Four new chalcohalides Ba3 AlQ4 X (Q = S, Se; X = Cl, Br) have been discovered by a conventional high-temperature method. All of them crystallize in the Pnma space group. The structure is composed of zigzag XBa layers and isolated AlQ4 tetrahedra. Detailed structural comparisons show that the cation size of the M IIIA metals and variable coordination modes of the Ba 2+ cations cooperatively influence the framework geometries of the title compounds. The first principles method was also used to investigate the electronic structures and optical properties. Their calculated birefringences range from 0.044 to 0.050 @1064 nm. Real space atom cutting analysis shows that the AlS4, GaS4, and InS4 tetrahedra make the main contribution to the birefringence.